Wood predictors in neotropical streams: Assessing the effects of regional and local controls in Amazon and Cerrado catchments. Issue 3 (7th December 2022) - de Oliveira Saraiva, Sarah; Kaufmann, Philip Robert; Rutherfurd, Ian; Gontijo Leal, Cecília; Pereira Leitão, Rafael; Rodrigues Macedo, Diego; Santos Pompeu, Paulo
Abstract: Large wood plays a critical role providing complex habitat structure in rivers and streams. The instream wood regime consists of wood recruitment, transport, retention, and decay in river corridors. In tropical streams, transport and decay are thought to be the dominant influences on the amount of instream wood stored, and these are driven by upstream forest cover, as well as catchment hydroclimatic and geomorphic characteristics. Lack of studies of the tropical wood regime leave many uncertainties. Notably, the wood regimes in the neotropical Amazon and Cerrado biomes are not known, and rapidly changing land use threatens efforts to understand their natural wood regime. We investigated predictors of instream wood in catchments of the Amazon and Cerrado subject to a wide range of agricultural land use to identify the critical factors controlling wood recruitment and load. Using the structural equation modelling technique, we disentangled the complex net of regional and local controls. Contrary to our expectations, local drivers—such as the relation between the piece size and channel dimensions, discharge, stream power, and riparian forest—were the most important predictors of instream wood. The amounts of wood found in these streams were primarily the result of the wood delivered by the local riparian forest and how much of that wood remains trapped. Therefore, the preservation of the forested riparian zones in Amazon and Cerrado streams is crucial for maintaining the sources of wood as well as the channel morphology capable of trapping and retaining instream wood. Further research should compare reference and disturbed streams to quantify the influence of anthropogenic activities on instream wood and its primary influences. This information would facilitate assessing the extent of human alteration and developing mitigating measures to arrest or reverse changes that reduce instream wood and degrade aquatic and riparian habitat in neotropical rivers and streams. Abstract : Regional variation in the amount of instream wood among streams was more strongly influenced by differences in transport than by differences in the amount of recruitment. Specifically, transport of wood recruited from the local riparian forest along these streams was controlled primarily by channel dimensions and the size of wood pieces relative to the channel size. Land use effects were manifested in changes in transport related to hydro alteration, channel incision, and the size of wood pieces entering the streams.